2009
DOI: 10.4103/0970-9290.57374
|View full text |Cite
|
Sign up to set email alerts
|

Coronally advanced flap in combination with acellular dermal matrix with or without enamel matrix derivatives for root coverage

Abstract: The application of EMD does not improve the clinical efficacy of ADM in combination with CAF in RC procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…It is clear that less traumatic procedures, with less chair time and involving only one surgical site, are preferred by most patients 1‐10,21‐27 . Independent of such preferences, most of the treated patients considered esthetics as their main concern, and in the great majority, the final outcomes of the performed surgical procedure (irrespective of inclusion of one or more surgical sites) fulfilled their personal expectations 1‐10,21‐27,30‐246 . However, differences among studies in terms of procedures, analysis (i.e., patient based or site based), sample size, follow‐up period, experience of operators, lack of baseline, and final recession characteristics prevent additional conclusions on this topic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that less traumatic procedures, with less chair time and involving only one surgical site, are preferred by most patients 1‐10,21‐27 . Independent of such preferences, most of the treated patients considered esthetics as their main concern, and in the great majority, the final outcomes of the performed surgical procedure (irrespective of inclusion of one or more surgical sites) fulfilled their personal expectations 1‐10,21‐27,30‐246 . However, differences among studies in terms of procedures, analysis (i.e., patient based or site based), sample size, follow‐up period, experience of operators, lack of baseline, and final recession characteristics prevent additional conclusions on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 101 articles 30‐131 with 94 RCTs potentially eligible for inclusion into the pooled estimates were identified in the base of evidence, and their main characteristics (i.e., number and age of participants, interventions, follow‐up period, number of sites exhibiting CRC, MRC [percentage], use of RMAs, randomization, allocation concealment, masking of examiners, completeness of the follow‐up period, and risk of bias) are depicted in Table 2 30‐131 . Seven studies were reported in two articles each, and their data were reported under one study name 37,38,57,58,65,66,83,84,90,91,110,111,115,116 …”
Section: Summary Of What Other Srs Have Evaluatedmentioning
confidence: 99%
“…Similar to previously conducted studies (40,41), the MTT assay was used to determine the effect of each restorative material on the cell viability or proliferation over a threeday time period. The results of the MTT assays are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…, Pourabbas et al. ) have found that EMD does not contribute to superior outcomes when associated with ADMG, in non‐smokers.…”
Section: Introductionmentioning
confidence: 96%